Giới thiệu điện ảnh Hàn Quốc (Korea, 2006)
This film documents the history and development of Korean filmmaking through these topics: 1. Melodramas: Korean sensibilities; 2. Grand theme of Korean cinema: a nation divided; 3. The artists of Korean cinema.
Keywords: Phim tài liệu,Documentary films; Hàn Quốc,Korea (South)